Field-effect Self-mixing Terahertz Detectors - Sun, Jiandong (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2016)
A comprehensive device model considering both spatial distributions of the terahertz field and the field-effect self-mixing factor has been constructed for the first time in the thesis. The author has found that it is the strongly localized terahertz field induced in a small fraction of the gated electron channel that plays an important role in the high responsivity. An AlGaN/GaN-based high-electron-mobility transistor with a 2-micron-sized gate and integrated dipole antennas has been developed and can offer a noise-equivalent power as low as 40 pW/Hz1/2 at 900 GHz. By further reducing the gate length down to 0.2 micron, a noise-equivalent power of 6 pW/Hz1/2 has been achieved. This thesis provides detailed experimental techniques anddevice simulation for revealing the self-mixing mechanism including a scanning probe technique for evaluating the effectiveness of terahertz antennas. As such, the thesis could be served as a valuable introduction towards further development of high-sensitivity field-effect terahertz detectors for practical applications.